INDONESIA AND ITS RELUCTANCE TO RATIFY THE UNITED NATIONS CONVENTION ON CONTRACTS FOR THE INTERNATIONAL SALE OF GOODS (CISG) - Oktaviandra, Surya (Indonesia Law Review, 2018)
There is still a huge debate on business policy in Indonesia pertaining the fact that the Government of Indonesia is still reluctance to ratify one of the important conventions for the business world namely CISG (Convention on Contracts for the International Sale of Goods). This paper attempts to discuss the issues which will deliver inter-disciplinary areas such as law, economics, and public policy. By analyzing this matter with a comprehensive measure, it will ensure an appropriate understanding and thus create more precise analysis to serve a contribution in suggesting solve-problem. Despite having its particular point of view, the author based and used other scholar`s arguments to compare and present the debate towards current business circumstance on practice, policy, and relevant regulations. The finding of this paper is either the current condition of business practice or global pressure are inadequate to force the immediate urgency to ratify the CISG. While the last option comes from the political will of government, the author believes that the government should seek to ratify the CISG in a convenient timing rather than alter the National Civil Code.